2021
DOI: 10.1093/jas/skab235.702
|View full text |Cite
|
Sign up to set email alerts
|

PSV-B-28 Late-Breaking: Development and validation of a Total Inflammation Index™ for identifying inflammation in Labrador Retrievers using a pressure walkway

Abstract: The objective of this trial was to develop an index system to identify inflammation in Labrador Retrievers using a pressure walkway system. Gait analysis data can be difficult to interpret between treatment groups or for identifying low grade inflammation. To calculate the Total Inflammation Index™, the distance away from the ideal score was calculated for four parameters for each dog, including gait lameness score, total pressure index, step/stride ratio, and hind reach. These values were equally weighted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Improvements in both pain assessments and gait analysis for undenatured type II collagen supplemented dogs agreed with the previously reported results of improved activity during runs and improved biomarker activity ( Varney et al, 2021 ). Reductions in cartilage oligomeric matrix protein (COMP) and pro-inflammatory cytokine interleukin-6 (IL-6) appear to be associated with improvement in the pain assessments and gait analysis.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Improvements in both pain assessments and gait analysis for undenatured type II collagen supplemented dogs agreed with the previously reported results of improved activity during runs and improved biomarker activity ( Varney et al, 2021 ). Reductions in cartilage oligomeric matrix protein (COMP) and pro-inflammatory cytokine interleukin-6 (IL-6) appear to be associated with improvement in the pain assessments and gait analysis.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study indicated that supplementation with undenatured type II collagen limits the development of pain and impaired mobility after exercise in Labrador Retrievers based on subjective pain assessments and objective gait analysis. Previously, we reported that supplementation of undenatured type II collagen limits the increase of pro-inflammatory and cartilage degeneration biomarkers in the serum of Labrador Retrievers after exercise ( Varney et al, 2021 ). During the same experiment, all dogs were scored using the pain assessments and gait analysis with results presented herein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations